Economic Impact of the Implementation of Chain of Custody (CoC) Certification in Sawmilling in Malaysia - Ab Ghani, Nor Suryani (2010)
Chain of Custody (CoC) certification has influenced the market of forestproducts since the establishment of forest certification in early the 1990s. CoC certification is one way for companies to promote and market their forest products from a sustainably managed forest. Furthermore, the supply and demand of certified forest products have also grown significantly corresponding to the increase in the numbers of certified companies. However, the costs of CoC certification are perceived to be crucial for the companies to become certified. The main objective of this study is to determine the costs of obtaining a CoC certification from the MTCC for sawmills and to estimate the economic impact of CoC certification in sawmilling in Malaysia. A survey was conducted on sawmilling companies with CoC certificate from the MTCC. The results from thedata analysis indicate that there exist three types of cost in obtaining the MTCCCoC certificates namely (i) cost to meet CoC standard or requirement, (ii) auditing cost and (iii) surveillance visit cost. Cost to meet the CoC standard is categorized as an indirect cost and was the major certification cost (95% of the total cost of certification) whereas auditing cost and surveillance visit cost are direct costs for the firms. It is argued that, these costs mainly depend on the size of the companies. However, the chi squares test has found that the relationship between costs of CoC certification with the size of companies, as measured by total workforce and annual sales turnover is not significant in the case of sawmills. Estimations of econometric relationships also shows that the cost in obtaining CoC certification for sawmills is not related to annual sales turnover,number of years in operation. But there was a statistically significant relationship between surveillance visit cost and the level of annual production. The second objective of this study is to ascertain the economic impact of CoC certification in the sawmilling industry in Malaysia. The input-output analysis showed that certified sawntimber has led to significant impacts on total output,income and employment to the Malaysia. These economic impacts were distributed in many sectors that helped to stimulate the nation’s economic growth. CoC certification can play an important role in the development of the Malaysian forest sector. Hence, effort should be made by relevant agencies to improve the certification process in order to minimize the costs and to enhance the benefits to sawmillers. Promotion should be enhanced to raise the adoption of CoC certification among timber industry. Ways and means have to be provided to support the holders of CoC certification to reap the benefits from certification.